Social capital at the outburst of the economic crisis in Greece, 2008-2010 - Irene Daskalopoulou (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2016)
Purpose - Social capital and its core components of social trust and associational activity are widely acknowledged as a core feature of strong and active civil societies that promote effective democratic governance and economic prosperity. Within this context the present study sets out to explore two important research questions. The first one relates to the stock of social capital characterizing Greece and its change during a highly sensitive era, that of the outburst of the economic crisis. The second research question relates to analyzing the group of civil servants as carriers of higher or lower levels of social capital compared to the other citizens. Design/methodology/approach - Based on the available knowledge in the field social capital is measured via the measurement of six main constructs comprising the soft and hard attributes of the concept, namely social trust, social altruism, equality, tolerance, humanitarianism and civic participation. Data are drawn from the European Social Value round 4 (2008) and round 5 (2010) surveys for Greece. Findings - Overall, empirical analysis indicates that the country experiences a statistically significant decline in its social capital level while public servants hold higher levels of social capital albeit also declining as for the rest of the country's citizens. Research limitations/implications - Important policy implications arise as a result of these findings related to issues of democratic legitimation and social participation. Originality/value - the research questions analysed here are important as they can help us sketch the country's profile with regard to the important concept of social capital that is highly associated with civil empowerment, democratization and increased civil participation levels.
Keywords: A13; D71; H83; 330; Social capital; social trust; civic participation; public servants